Aspects of acceptance: building a shared conceptual understanding - Mrazek, Michael D.; Dow, Bailey R.; Richelle, Justine; Pasch, Alexander M.; Godderis, Nathan; Pamensky, Talia A.; Rutila, Bryce A.; Mrazek, Alissa J. (Frontiers in Psychology, 2024)
Many contemplatives, scientists, and clinicians have pointed to the value of responding to life's difficulties by accepting experiences as they are. A growing body of research also suggests that acceptance contributes to effective coping with adversity, reduced stress, and improved emotional well-being. Yet within the scientific literature, there is little consensus on what acceptance means or how it should be measured. This makes it nearly impossible to synthesize empirical work on acceptance into a cohesive scientific understanding. Our goal in this paper is to clarify four facets of acceptance that are commonly referenced in research: acknowledging, allowing, non-judging, and non-attachment. We do not propose a specific definition of acceptance or even a set of privileged facets that must be included in future frameworks. We instead offer a vocabulary to facilitate productive communication among researchers that will, in turn, enable a more definitive scientific understanding of this important construct to emerge. After defining and explaining these aspects of acceptance, we further clarify these constructs in two ways. First, we illustrate how the four aspects are dissociable from one another. Second, we analyze their correspondence to related constructs from Acceptance and Commitment Therapy (ACT). Finally, we provide a concept worksheet that scholars can utilize to precisely operationalize acceptance in their own work.